Penilaian Tingkat Keaktifan Peserta Didik dalam Pembelajaran Sejarah Sebagai Peningkatan Mutu Pendidikan Nasional - Elfa Michellia Karima; Firza Firza; Wahidul Basri; Ray Silva (PATTINGALLOANG, 2021)
The introduction of the revised 2013 curriculum, which is currently being used in the education curriculum in Indonesia, has had a new impact, particularly on the activeness of students. However, a new problem arises when a very different learning system is applied directly to students, necessitating adaptation on the part of both students and teachers. The purpose of this study is to identify the learning model used by teachers at SMAN 2 Lumajang, as well as the level of student activity at SMAN 2 Lumajang in implementing the revised 2013 curriculum system. The teacher can make an assessment based on the level of student activity. The quantitative descriptive method is used in this study. Data was collected by distributing online questionnaires via Google form to students at SMAN 2 Lumajang, and a literature review was conducted to further deepen the study in this research. According to the findings of this study, the implementation of the revised 2013 curriculum that the government has proclaimed has not been fully successful due to the discovery of a low level of student activity when the revised 2013 curriculum policy was implemented, and the 2013 revised curriculum was not fully implemented as it had been prepared, because there was still no alignment with the conditions of the students being taught. As a result, there is a need for the government to conduct a review of the revised 2013 curriculum in order to improve the quality of national education.